Multidrug-Resistant Shigella Infections in Patients with Diarrhea, Cambodia, 2014–2015 - Poramathikul, Kamonporn (Emerg Infect Dis, 2016)
We observed multidrug resistance in 10 (91%) of 11 Shigella isolates from a diarrheal surveillance study in Cambodia. One isolate was resistant to fluoroquinolones and cephalosporins and showed decreased susceptibility to azithromycin. We found mutations in gyrA, parC, β-lactamase, and mphA genes. Multidrug resistance increases concern about shigellosis treatment options.